Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3390/rs6042745
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Correction of ZY-3 Satellite Images and Its Effects on Estimation of Shrub Leaf Biomass in Mountainous Areas

Abstract: Abstract:The availability of ZY-3 satellite data provides additional potential for surveying, mapping, and quantitative studies. Topographic correction, which eliminates the terrain effect caused by the topographic relief, is one of the fundamental steps in data preprocessing for quantitative analysis of vegetation. In this paper, we rectified ZY-3 satellite data using five commonly used topographic correction models and investigate their impact on the regression estimation of shrub forest leaf biomass obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
2
27
0
4
Order By: Relevance
“…The improved cosine correction shows a small overcorrection in Figures 5d,l, and 6d,l, which is caused by the Lambertian reflectance assumptions. Many studies have reported similar behavior in the cosine correction method [10,13,14,63]. Among the five methods investigated here, the …”
Section: Evaluation Of Topographic Correction Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…The improved cosine correction shows a small overcorrection in Figures 5d,l, and 6d,l, which is caused by the Lambertian reflectance assumptions. Many studies have reported similar behavior in the cosine correction method [10,13,14,63]. Among the five methods investigated here, the …”
Section: Evaluation Of Topographic Correction Methodsmentioning
confidence: 88%
“…Our results indicate that the C-correction, SEC, and VECA methods show the best performance with both DEMs. The improved cosine correction consistently overcorrects the imagery, as a result of the Lambertian reflectance assumptions [10,13,14,63]. Additionally, the algorithm for this method considers the mean illumination for forest strata instead of regression parameters calculated from the illumination and uncorrected reflectance [5].…”
Section: Topographic Correction and Demsmentioning
confidence: 99%
“…Как сообщается в работе [9], топографическая коррекция, которая устраняет различные эффекты, вызванные наклоном местности, является важным этапом в предварительной обработке бортовой инфор-мации.…”
Section: анализ литературных данных и постановка проблемыunclassified
“…Согласно [9], топографическая коррекция пред-ставляет собой транспортирование радиационных яр-костных данных или данных об отраженной радиации пикселей на наклонной плоскости в данные другой опорной плоскости с целью устранения топографиче-ских эффектов. При этом, один и тот же объект имею-щий различные азимутальные координаты по Солнцу должен иметь одинаковые спектральные реакции.…”
Section: анализ литературных данных и постановка проблемыunclassified
“…Previous studies have compared these models under different conditions [1], [6], [7], but their performance is site dependent, and currently, no topographic normalization model is generally accepted. Good performance appears to only occur in relatively small study sites when using one global parameter for all pixels from one band image [1] or when complex prestratification approaches were used under conditions where the relationship between the spectral signature and an IC can be assumed topography specific or illumination specific [8], or land cover specific [9].…”
Section: Introductionmentioning
confidence: 99%